SIBAKO ANALYSIS (Product Mix Innovation Strategy and Collaboration) IN FACING COMPETITIVENESS IN THE HYPERCOMPETITIVE ERA OF 2025 AT PT. IEMAHKAI WOOD ART MAJENANG – CILACAP - Enas; Eti Trisnawati (Proceeding of International Seminar on Agricultural Conservation and Cultural Heritage, 2025)
This research is motivated by the rapid development of the business world and increasing business competition. in the era of globalization and technological advances, companies experience challenges and demands in developing and improving the company’s competitive advantage. This research method uses a qualitative approach, with data collection from interviews, observations and documentation studies and Triangulation. The results of the study show that: first; Conducting an analysis of product mix innovation strategies and collaboration in the rapid and tight development of the world today is an important element for companies to survive and exist in the hypercompetitive era. Second; The problems faced are the high level of business competition both offline and online , as well as rapid and unpredictable changes in market dynamics, companies are required to continue to innovate, especially in strategy mix product And collaboration For maintain Power competition And relevance in increasingly competitive market. Third; The solution used to describe the problem is to create, develop and perfect various product elements such as variation, quality, design, added value to face market competitiveness and rapidly changing market needs. In addition to the product mix innovation strategy, collaboration strategies with external parties such as: business partners, distributors, other companies, supplier, platform technology and digital Ecosystem, government And institution education Which become key to accelerating innovation, expanding distribution and accessing resources that the company does not yet have internally. Collaborating can create synergies to increase competitive advantage and create a more adaptive business ecosystem for the company.